(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Anita Desai is one of the most powerful contemporaryIndian Novelists in English. Her interpretation of man-woman relationship isinfluenced and conditioned by complex social milieu. Mostly woman areculturally as well as emotionally dependent on man and any disruption inrelationship proves to be a loss of self. In this paper we present about man womenrelationship in Anitha Desai novel.